2012
DOI: 10.1016/j.oraloncology.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of microRNA-9 is a specific and sensitive biomarker for oral and oropharyngeal squamous cell carcinomas

Abstract: summary Detection of DNA methylation has produced promising results as biomarkers for head and neck squamous cell carcinoma (HNSCC). However, current panels are limited by an insufficient number of sensitive and specific tumor markers. MicroRNAs (miR) play an important role in tumorigenesis, and may represent a novel panel of molecules for the development of cancer biomarkers. We investigated methylation of three miRNA promoter sites of miR-9 (miR-9-1, miR-9-2, miR-9-3) in 107 human head and neck tissue sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 28 publications
5
62
0
3
Order By: Relevance
“…In normal head and neck tissue, miR-9-positive cells were undetectable ( Figure 6A), however in head and neck SCCs, 13 of 64 samples (21%; Table 1) contained sporadic miR-9-positive cells (not shown). This low incidence of miR-9-positive tumors is consistent with the recent finding that miR-9 is often methylated in SCCs (44). In contrast, however, 67% (50 of 75) of SCC lymph node metastatic lesions contained miR-9-positive cells ( Figure 6A and Table 1).…”
Section: K15kras G12d Smad4 -/-Sccs Retained Csc Populations But Msupporting
confidence: 90%
See 2 more Smart Citations
“…In normal head and neck tissue, miR-9-positive cells were undetectable ( Figure 6A), however in head and neck SCCs, 13 of 64 samples (21%; Table 1) contained sporadic miR-9-positive cells (not shown). This low incidence of miR-9-positive tumors is consistent with the recent finding that miR-9 is often methylated in SCCs (44). In contrast, however, 67% (50 of 75) of SCC lymph node metastatic lesions contained miR-9-positive cells ( Figure 6A and Table 1).…”
Section: K15kras G12d Smad4 -/-Sccs Retained Csc Populations But Msupporting
confidence: 90%
“…miR-9-positive cell numbers are increased in metastatic human primary SCCs and SCC metastases. It has been reported that miR-9 is frequently methylated in human cancers, including SCCs, and as such, miR-9 has been suggested to be a tumor suppressor (42)(43)(44). The effect of miR-9 on the metastatic behavior of SCCs observed in our animal model and in the human SCC cell lines prompted us to examine whether miR-9 was elevated in human SCCs.…”
Section: K15kras G12d Smad4 -/-Sccs Retained Csc Populations But Mmentioning
confidence: 82%
See 1 more Smart Citation
“…Reduced miR-9 expression was associated with the methylation of miR-9 in tumor tissues. The methylations of miR-9-1 and miR-9-3 are sensitive and specific biomarkers for HNSCC, particularly for oral and oropharyngeal squamous cell carcinomas (39). The mechanisms for the downregulation of miR-99a in OSCC remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…miR-9 down-regulation is considered a poor survival marker in cervical cancer (15), lung squamous cell carcinoma (17), and in acute lymphoblastic leukemia (21), and it was associated with development of cancer metastasis (19,(22)(23)(24). Silencing of miR-9 by cytosine-phosphate-guanine (CpG) island hypermethylation was found in many tumors (16,17,(21)(22)(23)25), clearly indicating that miR-9 possesses tumor suppressor features. However, the molecular mechanism leading to miR-9 silencing in cancer has not been defined.…”
mentioning
confidence: 99%